Investigation of mechanical properties on Mg/TiC/graphite hybrid composites fabricated by powder metallurgy techniques. (2022) - Suriyaprakash, M.; Nallusamy, M.; Kiran, K.; Rajkumar, S.
Abstract: Presently, the composite materials are progressively replacing the conventional alloys in various industrial applications such as aerospace, automobile, automotive and marine industries due to its excellent mechanical, chemical, tribological and thermal properties. In this study, Magnesium (Mg) hybrid composites reinforced with the calculated weight percentages (wt.%) of Titanium carbide and graphite have been fabricated using spark plasma sintering which is one of the most popular and efficient techniques of powder metallurgy. The effect of mechanical properties such as microhardness on the fabricated Mg/TiC/graphite hybrid composites has been calculated. Among the three Combination of Composites Tungsten Carbide 3 wt%, Graphite 3 wt% and balance Magnesium is found to be Higher hardness value of 157.The grain boundaries of Mg, uniform dispersion of reinforcement particles, dislocation defects and strengthening of inter-metallic bond between the matrix and reinforcement materials have been observed using the micrographs of Scanning Electron Microscope (SEM). The effects of SEM microstructures have been observed and discussed.